Effectiveness of Digital Sharia Pawnshop Services in Increasing The Number of Customers Pegadaian Syariah - Alfian, Ian Ian; Siregar, Erpiana (Journal of Islamic Financial Technology, 2023)
Technology continues to develop, this is proven by technological advances in the form of applications and online transactions. However, not all technology provides convenience and has a positive impact on its users if not handled properly. Therefore, this thesis aims to reveal the effectiveness of the online services provided by Pegadaian Syariah Siringo-ringo through the Pegadaian Syariah Digital Service (PSDS) Application Service in increasing the number of customers. The background to the problem in this research is that errors often occur in applications and services that do not comply with procedures. The data collection method uses qualitative methods with observation, interviews and documentation.The research results show that this application is largely operating according to its intended use, although it is not yet fully effective in facilitating transactions. This application is not really effective in increasing the number of customers because customers still have minimal knowledge regarding the function of this application. Then the increase in the number of customers did not increase too much, but there continued to be an increase every year, be it gold savings customers, pawnshops, etc.